2021
DOI: 10.5039/agraria.v16i3a9317
|View full text |Cite
|
Sign up to set email alerts
|

Elephantgrass, a tropical grass for cutting and grazing

Abstract: Elephantgrass (Pennisetum purpureum Schum. syn. Cenchrus purpureus) is one of the most important forage plants worldwide, cultivated in almost all tropical and subtropical regions due to its high potential for dry matter production, nutritional value, acceptability by different animal species and categories, vigor, and persistence. It has shown great potential for biomass energy production and other forms of non-forage use. This study aimed to review the current knowledge about the cultivation and use elephant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
20

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 32 publications
0
12
0
20
Order By: Relevance
“…Souza et al (2021) reported lower ADF content in leaves of dwarf Mott than dwarf Taiwan (296 vs 338 g/kg DM) when assessing these genotypes in cut-andcarry systems under rainfed conditions. We also recorded lower ADF contents in dwarf Mott than in the dwarf Taiwan genotype, probably because of the higher leaf:stem ratio and shorter internodes (Pereira et al 2021).…”
Section: Herbage Nutritive Value and Protein Fractionationmentioning
confidence: 75%
See 3 more Smart Citations
“…Souza et al (2021) reported lower ADF content in leaves of dwarf Mott than dwarf Taiwan (296 vs 338 g/kg DM) when assessing these genotypes in cut-andcarry systems under rainfed conditions. We also recorded lower ADF contents in dwarf Mott than in the dwarf Taiwan genotype, probably because of the higher leaf:stem ratio and shorter internodes (Pereira et al 2021).…”
Section: Herbage Nutritive Value and Protein Fractionationmentioning
confidence: 75%
“…The N fertilisation performed via urea application only in the monocropping system contributed to greater HA in Elephant B grown as monocrop than intercropped with butterfly pea. The tall Elephant B has high N-use efficiency for HA, mainly because of rapid stem elongation (Silva et al 2018;Pereira et al 2021). Nevertheless, such differences were not verified in the other monocrop-intercrop comparisons.…”
Section: Herbage Accumulationmentioning
confidence: 92%
See 2 more Smart Citations
“…Elephant grass [ Cenchrus purpureus (Schumach.) Morrone]is widely used as a key forage plant in ruminant production in tropical and subtropical regions due to its favourable soil and climate conditions that result in high growth rate, high forage production, and great nutritional value (Vander Pereira et al, 2021).…”
Section: Introductionmentioning
confidence: 99%